Pemanfaatan Bahan Ajar Berbasis Kearifan Lokal Dalam Pembelajaran Sains Di Sekolah Dasar - Indriyani Indriyani; Nurul Anisa; Irma Sari; Minawar Minawar; Riski Andrianingsih (Prodi PGSD Unsultra, 2024)
The use of local wisdom-based teaching materials in science learning in elementary schools offers a relevant and contextual approach to improving students' understanding of science. This article aims to explore the literature related to the integration of local wisdom in science learning, focusing on its impact on students' understanding, environmental awareness, and the development of science skills. This study shows that the use of local wisdom can enrich teaching materials, increase student engagement, and foster an attitude of caring for the environment. The method used in this article is a literature study by analyzing various studies related to local wisdom in the context of science education. It was found that despite challenges in implementation, local wisdom-based teaching materials provide significant benefits in a more inclusive and relevant learning context for elementary school students.